Pudendal neuralgia after pelvic surgery using mesh: Case reports and laparoscopic pudendal nerve decompression. (2nd June 2016) - Sancak, Eyup Burak; Avci, Egemen; Erdogru, Tibet
Abstract: Persistent pain after vaginal mesh surgery is a rare and agonizing entity that has devastating consequences for the patient's quality of life. Many etiologies have been blamed including nerve injuries and entrapments. Pudendal neuralgia is a rare chronic neuropathic pain syndrome in the anatomical territory of the pudendal nerve. Various treatment options, such as medication management, physiotherapy, nerve blocks, decompression surgery and neuromodulation, have been used, but the most appropriate treatment for pudendal neuralgia has not yet been determined. In this article, we present two cases of postoperative pelvic pain thought to be secondary to injury or mechanical distortion of the pudendal nerve after rectocele repair using mesh and tension‐free vaginal tape sling. In cases of failed conservative treatment and of mesh removal surgery, laparoscopic pudendal nerve decompression and omental flap wrapping operation can be a treatment option for pudendal neuralgia.